Performance analysis of stacked capacitive antenna for lightning remote sensing - Ong, J. Y. (2019)
Antennas are the important elements in the lightning detection system. To improve performance of the lightning detection system, it is so necessary to improve the efficiency of the antennas. There are two types of antennas used in the system which are capacitive antenna for electric field sensing and loop antenna for magnetic field sensing [1]. Both of these antennas are big in size and causing inconvenient during set up. Thus, small and portable antennas are designed. It is so important to remain or improve the sensitivity of the antennas even though it is small in size. Stacking method is used in capacitive antenna by increase copper plate layer in between the parallel plate antenna. After prototype the multi-stacked capacitive antenna, performance analysis is carried out. Performances of the antennas are compared using CST simulation and hardware set up. Multi-stacked capacitive antenna is compared with the single plate antenna and found that the performance of the antenna increases as the stacked number increases.